(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Corporate Governance has become a ―buzz word‖ nowadays. All thanks to Liberalization andglobalization that have led to the renaissance of the concept of Corporate Governance all across theglobe. It is based on the dictum of accountability, transparency and quality. Banking as is different fromother forms of business has commonly been treated as a matter of public interest given its overallimportance to the economy both in regard to its linkages with the real sector and for providing apayments and settlement system. The constant efforts made by the Reserve Bank of India and thegovernment to improve the state of governance in banking sector cannot be said to be nugatory but itsefficiency is still surrounded by questions. This paper critically analyses the existing governancepractices in the banks across the country in the light of the financial position of the banks in the lastdecade elaborating on the issues of governance in banks and the consequences the banks are facingon account of poor corporate governance in the banking industry. It also examines the viability of theexisting legislative framework and the efficiency of the actions taken with regards to governance by theregulatory authorities.